Anger and Sadness as Moral Signals. Issue 2 (March 2022) - Plaks, Jason E.; Robinson, Jeffrey S.; Forbes, Rachel
Three studies examined the relationship between emotions and moral judgment from an interpersonal perspective. In Studies 1 and 2, participants justified their decisions in sacrificial dilemmas to an imagined interlocutor. Linguistic analyses revealed that Don't Sacrifice justifications contained more anger-related language than sadness-related language, whereas Sacrifice justifications contained roughly equal proportions of anger and sadness language. In Study 3, participants made character inferences about an actor who chose to/refused to sacrifice one person to save multiple people. We manipulated the actor's ratio of anger to sadness. Participants rated the Don't Sacrifice actor more negatively when they displayed high anger relative to sadness but rated the Sacrifice actor negatively whenever they exhibited high anger (independent of sadness). These data highlight novel ways in which actors and observers use emotions to complement the substance of a moral argument.